We're all wonders - Palacio, R. J. (New York : Alfred A. Knopf, 2017)
Augie enjoys the company of his dog, Daisy, and using his imagination, but painfully endures the taunts of his peers because of his facial deformity.
1.4
K-3
AD370L
N
Keywords: Abnormalities, Human -- Fiction; Self-acceptance -- Fiction; Teasing -- Fiction; Dogs -- Fiction; Birth defects -- Fiction; Self-acceptance -- Fiction; Teasing -- Fiction; Dogs -- Fiction